The Ah Beng subculture: a popular view - Chan, Suet Kay (2010)
There is a trend among Malaysians in using the Hokkien term ‘Ah Beng’, in describing unsophisticated people. ‘Ah Beng’ means quite simply, a ‘country bumpkin’. However, there has not been any academic studies on the subject in Malaysia, whereas popular media tout it as a cultural icon. There are some issues related to the use of this term – for example, do people readily identify themselves as ‘Ah Beng/Ah Lian’ or is it a pejorative term? Furthermore, among Malaysian Chinese there is a divide between the English-speaking and Chinese-speaking groups. Do the English speaking groups deliberately conjure up a term to disassociate themselves from their Chinese-speaking counterparts, for fear of being seen as unmodernised? And why do the Chinese speaking Malaysian Chinese display these characteristics ‘mocked’ by the non-Chinese speaking Chinese – which include traits like the overt display of Western brand names, copying trends from East Asia, persistently sticking to their own mother tongue, and displaying a form of anti-intellectualism? In Singapore however, leading sociologist Chua Beng-Huat has spearheaded much of the academic literature on the ‘Ah Beng’, and charts its rise from ‘stereotype’ to a desirable subculture. This paper surveys the general public opinion in urban Malaysia of the concept of ‘Ah Beng’, using a total of 200 respondents from the urban youth in Kuala Lumpur.